Development of Mobile Games-Based Social Studies Instructional Media to Develop 21st Century Skills - Gandung Wirawan; Aim Abdulkarim; Kokom Komalasari; Erlina Wiyanarti (STKIP Singkawang, 2023)
Facts show that not all educators are able to optimize information technology facilities according to the learning needs and characteristics of students in social studies learning after the Covid-19 pandemic. Social studies learning will have a number of significant issues if it is not adjusted to the characteristics of students of generation Z, by which their daily life is influenced and dependent on gadgets. The purpose of this research is to produce a mobile game based social studies instructional media that is able to develop students’ 21st century skills. This study uses the Research and Development method with research stages using the ADDIE design model (Analysis, Design, Development Implementation and Evaluation). The results showed that the media get recommendations with eligibility criteria for use from experts of media and social studies materials validators with an average score of 4.11. The study is implemented with a quasi-experimental design in class 8A as the Experiment class and Class 8C as the control class. With the significance of 0.000 < 0.05, social studies instructional media based on mobile games is effectively used to develop 21st century skills. It is concluded that mobile game-based social studies instructional media has been proven to effective in developing students' 21st century skills.